Did I get these questions right?

I' trying to follow the PEMDAS order, but it doesn't seem to always work out.

2 + [3 + 5 (2 + 1) ]=

**78.2**

3 - 2 * 4 / 2 =

**2**

6 { 3 + 5 / 2] =

**33**

9 - 4 (3 + 6 * 2) = __ + 1 =

**76**

9 - 4 (3 + 6 * 2) =

**75**

6 + {5 - [2 + (3 - 1) ] } =

**7**

6 - { 4 - [ 2 - (6 +20) ] } =

**30**

And then there's something as simple as:

3 - 5 (2 - 4)

I know first, it would be 2 - 4 = -2.

But I'm not sure if I should multiply the parenthesis by BOTH 3 and 5, or just multiply 5 by the parenthesis, THEN subtract that number from 3?

This is where the problem lies. Any help would be great, thanks.